Penyuluhan Kesehatan terkait Kesehatan Mental pada Remaja - Rasniah Sarumi; Narmi Narmi (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2022)
Several types of mental disorders are commonly found, including depression, bipolar disorder, anxiety, post-traumatic stress disorder (PTSD), obsessive compulsive disorder (OCD), and psychosis. Some mental illnesses only occur in certain types of sufferers, such as postpartum depression which only affects women after giving birth. The research objective is to increase students' understanding of the importance of maintaining mental health. The method of implementation is by conducting a pre-post test. The conclusion is that the output obtained from this activity is that students at SMK Negeri 1 Muna know and understand how to deal with mental health problems so that students are able to make efforts to protect against things that can lead to dangerous actions such as self-harm, analysis techniques and activity results